A hybrid simulation modeling framework for regional food hubs. Issue 1 (2nd January 2019) - Mittal, Anuj; Krejci, Caroline C.
Abstract: As demand for regionally produced food has increased, regional food hubs have helped to facilitate connections between consumers and small-scale food producers. However, food hubs often struggle to achieve the logistical and operational efficiencies that characterize conventional large-scale food distribution. In many cases, implementation of innovations adopted by conventional food distributors has proved to be challenging and even counterproductive for food hubs, due to their distinct business structure and mission. To address this problem, an empirical agent-based and discrete-event hybrid simulation model was developed to determine the effects of incorporating various efficiency-enhancing practices into food hub warehousing operations. The model was validated using data from a food hub in central Iowa. Experimental results demonstrate the potential usefulness of this model in supporting food hub managers' operational planning decisions, as well as the effectiveness of incorporating agent-based and discrete-event simulation modeling paradigms to study warehousing operations.